TRASH4CASH: a high-impact recycling initiative at UiTM Kedah - UiTM, UGC (UiTM Green Centre, 2025)
The TRASH4CASH programme was part of the recycup initiative, a final project for fifth-semester Diploma in Office Management and Technology (BA132) students enrolled in the organising event course (OBM310) at UiTM Kedah. with the theme “Green, Health, and Wellness,” the programme aimed to raise awareness of environmental sustainability through recycling practices.